Potensi Aktinidin sebagai Pelunak Daging - Warsono El Kiyat (Universitas Merdeka Madiun, 2019)
This study aimed to discuss the activity of actinidin in meat tenderization and to understand the ability of actinidin as a substitute for other tenderizing enzymes such as papain. Actinidin could be found in kiwi fruits with a similar structure and proteolytic activity characteristics to papain. The proteolytic activity of actinidin was found to be able to substitute papain in meat tenderizing without creating an off flavor side effect. However, increasing the actinidin concentration could enhance its proteolytic activity. Besides, actinidin also has the ability to hydrolyze collagen proteins and fibrinogens perfectly compared to papain activity.